REUNDERSTANDING HOW TO TEACH ENGLISH GRAMMAR FOCUSING ON THE PROCEDURAL KNOWLEDGE - Veni Roza (Universitas Negeri Padang, 2013)
The fact is among teachers, grammar and learners. The teacher gives a grammatical rule followed by a set of exercise designed to clarify the grammatical point and help the learners master the point. That is called by deductive method. Or teachers present the learners with samples of language and through a process of guided discovery, get them to solve the rule for themselves. The last is inductive procedures. These ways in the classroom do not make them able to communicate in the target language. They can give or know explanation of the grammatical rule but violate the rule when using language communicatively. For example a learner can tell me the formula of passive, when making statement in passive and why it is in passive he isn’t able. Now, how we as English teachers reunderstand that the focus of teaching grammar is on the development of procedural rather than declarative knowledge. Our task is to give learners a proper context for the grammar point. It means that we teach grammar in order not only to know language rules but also to be able to use the knowledge for communication.